Factores personales e institucionales que influyen en el enfermero en la aplicación del proceso de atención de enfermería: Revisión narrativa. (2022)
Introduction: The Nursing Care Process (NCP) is the systematic structure that facilitates and focuses the care of people, its applicability corresponds in the identification of the needs of them in order to focus activities that influence in the positive way to recover of the patient, to make this possible, we found that the NCP includes important stages and if these stages are avoided these will have repercussions on the care and health condition of the patient. Aim: To identify the personal and institutional factors that influence the nursing professional in the application of the nursing care process. Methodology: A integrative review was carried out through the extraction and careful selection of scientific articles found in the following health databases: "Lilacs, Pubmed, Scielo, Ovid and Medigraphic" that corresponded to the objective of our research. To develop it, we used the methodology structure created by Whittemore and Knafl, where a series of stages were mentioned and allowed a detailed analysis of the literature and delimitation of the information, through a matrix, tables and graphs that synthesized the information. Results: Brazil and Africa countries were the main exponents; 42.3% of the articles were qualitative studies, 23.1% were quantitative studies; the sources with the highest results correspond to Pubmed, Redalyc and Lilacs. Ten categories were identified; five belong to personal factors and five belong to institutional factors. Conclusion: There are personal and institutional factors that influence in a negative way the appropriate and optimal development of the individualized nursing care process with each patient. Among the first ones, we have: Education, motivation, experience, recognition of the NCP and adaptation of the staffs. The seconds include lack of incentives, stressful environment, lack of resources, lack of institutional recognition of the NCP and supervision of its applicability.